Effects of coarse cereals on dough and Chinese steamed bread – a review - Yang, Yunfei; Wang, Xinwei (Frontiers in Nutrition, 2023)
Chinese steamed breads (CSBs) are long-established staple foods in China. To enhance the nutritional value, coarse cereals such as oats, buckwheat, and quinoa have been added to the formulation for making CSBs. This review presents the nutritional value of various coarse cereals and analyzes the interactions between the functional components of coarse cereals in the dough. The addition of coarse cereals leads to changes in the rheological, fermentation, and pasting aging properties of the dough, which further deteriorates the appearance and texture of CSBs. This review can provide some suggestions and guidelines for the production of staple and nutritious staple foods.